2017
DOI: 10.1007/s10886-016-0807-7
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Differences in Herbivore-Induced Plant Volatile Blends from Tomato Plants Infested by Either Tuta absoluta or Bemisia tabaci

Abstract: Plants release a variety of volatile organic compounds that play multiple roles in the interactions with other plants and animals. Natural enemies of plant-feeding insects use these volatiles as cues to find their prey or host. Here, we report differences between the volatile blends of tomato plants infested with the whitefly Bemisia tabaci or the tomato borer Tuta absoluta. We compared the volatile emission of: (1) clean tomato plants; (2) tomato plants infested with T. absoluta larvae; and (3) tomato plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 70 publications
8
72
0
2
Order By: Relevance
“…Similarly, to most of the individual compounds, the total volatiles released by undamaged and host-infested flowering melons did not differ statistically. Unlike tissue-damaging herbivores, phloem-feeders stimulate the emission of smaller quantities of volatiles compared to intact plants, and at times no changes may be detectable (Du et al 1998;Turlings et al 1998;Rodriguez-Saona et al 2003;Silva et al 2017), due to the minimal leaf injury inflicted and to salivary effectors that prevent the synthesis of volatiles (Walling 2008). Although Desurmont et al (2015) showed that herbivory induces much smaller amounts of leaf volatiles in flowering than in vegetative plant stages, parasitic wasps are still able to recognize nuances of plant-blend composition in order to effectively locate their host (Bruce et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, to most of the individual compounds, the total volatiles released by undamaged and host-infested flowering melons did not differ statistically. Unlike tissue-damaging herbivores, phloem-feeders stimulate the emission of smaller quantities of volatiles compared to intact plants, and at times no changes may be detectable (Du et al 1998;Turlings et al 1998;Rodriguez-Saona et al 2003;Silva et al 2017), due to the minimal leaf injury inflicted and to salivary effectors that prevent the synthesis of volatiles (Walling 2008). Although Desurmont et al (2015) showed that herbivory induces much smaller amounts of leaf volatiles in flowering than in vegetative plant stages, parasitic wasps are still able to recognize nuances of plant-blend composition in order to effectively locate their host (Bruce et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, infestation by T. absoluta has been demonstrated to induce the emission of HIPVs [23,24]. In addition, egg deposition by T. absoluta seems to induce the release of OIPVs by tomato plants [25].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, wild tomato relatives produce a broader set of defence‐related volatile organic compounds compared with domesticated varieties (Lundgren et al ., ) and volatiles produced by wild tomatoes are less attractive and can repel the pest, Tobacco whitefly, compared with domesticated tomatoes (Bleeker et al ., ). Yet, volatiles produced after herbivory are important for the attraction of natural enemies in domesticated tomato (Tan & Liu, ; Silva et al ., ) and differences in volatile production by wild and domesticated crops will likely influence both pest and predator responses. However, it is unknown whether pest and predators commonly diverge in their responses to domesticated crops and the traits associated with domestication, particularly for indirect defences.…”
Section: Introductionmentioning
confidence: 99%